Voltage stability index improvement system by optimal placement of STATCOM in distributed systems - Ms. Shweta Chourasia , Dr I.D Soubache,Dr.P.Gomathi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
To provide the needed load, an interlinked radial distribution network includes a high amount of nodes and branchings. In the context of Pakistan, increased electrical demand places excessive stress on the radial distribution network, affecting the overall network's performance and potentially leading to voltage collapse; hence, it is desirable to keep the voltage at each bus within allowed limits. To tackle voltage stability indices concerns, several technologies such as STATCOM and other downstream linked devices are used, however proper sizing and location is also a key obstacle in the network. This study provides a Particle Swarm Optimization approach that finds the optimum position and configuration of STATCOM to be deployed on the real-time distributor by identifying the voltage regulation for the lowest bus in the network. The installation of STATCOM in the right area increased the voltage stability index (VSI), effectively reduced energy loss, and boosted the voltage stability, according to the results.